Regulação da temperatura corporal : sensores e efetores térmicos - Scarpellini, Carolina da Silveira (2016)
In this study, we aimed at investigating the involvement of the warmth-sensitive channel – TRPV4 (in vitro sensitive to temperatures in the range of approx. 24–34°C) – on the thermoregulatory mechanisms in rats. We treated rats with a chemical selective antagonist (HC-067047) of the TRPV4 channel and measured core body temperature, metabolism, heat loss index and preferred ambient temperature. The behavioral mechanism was also assessed after treatment with topical agonist (RN-1747). Our data revealed that intravenous blockade of this channel with HC-067047 caused an increase in core body temperature at ambient temperature of 26 and 30°C, but not at 22 and 32°C. At 26°C, HC-067047-induced hyperthermia was accompanied by increase in oxygen consumption (an index of thermogenesis). Furthermore, rats chemically stimulated with TRPV4 agonist choose colder ambient temperatures and the cold-seeking behaviour after thermal stimulation (28–31°C) was inhibited by TRPV4 antagonist. Our results suggest, for the first time, that TRPV4 channel is involved in the recruitment of behavioural and autonomic warmth-defence responses to regulate core body temperature.